EXTENDING LIBRE OFFICE WORD PROCESSOR FOR CITING HOLY QURAN AND HADITH SHARIF USING FAST STRING SEARCH ALGORITHMS - Mallek HANNACHI; Insaf SAIDIA (My University, 2024)
Word processors with strong features for producing, editing, and formatting documents, such as Libre Office are essential for document management. For theological and cultural reasons, quoting Quranic verses is essential for Muslims. Our project's objective is to create a LibreOffice extension that will make it easier to facilitate the insertion of Quranic text into documents while preventing transcription errors. Users can select verses or ranges from Surahs and search for matching Ayat. This extension uses a faststring search method similar to Boyer-Moore for effective functionality. ----------------------------------------------------------------------------- تعتبر برامج معالجة الكلمات ذات ميزات قوية لإنتاج وتحرير وتنسيق الوثائق، مثل LibreOffice، ضرورية لإدارة الوثائق في وقتنا الحالي. لأسباب دينية وثقافية، فإن الاقتباس من الآيات القرآنية ضروري للمسلمين. هدف مشروعنا هو إنشاء امتداد LibreOffice الذي يعمل على تسهيل إدخال النص القرآني في المستندات مع منع أخطاء النسخ. يمكن للمستخدمين اختيار آيات أو أجزاء من السور والبحث عن مطابقة الآيات. يستخدم هذا الامتداد خوارزمية البحث السريع بوير-مور للوظائف الفعالة. ----------------------------------------------------------------------------- : Les éditeurs de texte dotés de fonctionnalités puissantes pour produire, éditer et formater des documents, tels que LibreOffice, sont essentiels pour la gestion des documents. Pour des raisons théologiques et culturelles, citer des versets coraniques est essentiel pour les musulmans. L’objectif de notre projet est de créer une extension LibreOffice qui facilitera l’insertion de texte coranique dans les documents tout en évitant les erreurs de transcription. Les utilisateurs peuvent sélectionner des versets de sourates et rechercher un ayat correspondant. Cette extension utilise une méthode de recherche de chaîne rapide similaire à Boyer-Moore pour une fonctionnalité efficace.